1990
DOI: 10.1148/radiology.176.3.2202010
|View full text |Cite
|
Sign up to set email alerts
|

Renal functional response to dopamine during and after arteriography in patients with chronic renal insufficiency.

Abstract: The potential renal vasodilatory effect of dopamine in improving renal function after arteriography was studied. Sixty patients with preexisting renal insufficiency were prospectively randomized into two groups. Patients in the treated group (n = 30) received an infusion of dopamine for 12 hours starting at the beginning of arteriography. Patients who received placebo infusion with arteriography (n = 30) served as controls. The study was conducted in two different time intervals. In the first interval, serum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…The study by Kapoor et al was the only study included in this meta-analysis that showed a beneficial effect of low-dose dopamine [41]. However, the four other studies included in this meta-analysis that studied the reno-protective effects of low-dose dopamine in patients receiving contrast media did not replicate these findings [39,40,42,43]. Indeed, by subgroup analysis, low-dose dopamine had no significant effect on renal function in patients receiving radiocontrast media (-11.8; 95% CI -34.4, 10.6; P=0.3).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The study by Kapoor et al was the only study included in this meta-analysis that showed a beneficial effect of low-dose dopamine [41]. However, the four other studies included in this meta-analysis that studied the reno-protective effects of low-dose dopamine in patients receiving contrast media did not replicate these findings [39,40,42,43]. Indeed, by subgroup analysis, low-dose dopamine had no significant effect on renal function in patients receiving radiocontrast media (-11.8; 95% CI -34.4, 10.6; P=0.3).…”
Section: Discussionmentioning
confidence: 86%
“…Of these, six were excluded; the remaining 15 trials [8, 30,31,32,33,34,35,36,37,38,39,40,41,42,43] were included in this meta-analysis. Articles were excluded for the following reasons: dopamine was combined with another agent [44,45,46], outcome variables not recorded [47], and pediatric patients were studied [48,49].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to findings of those researchers, two prospective trials have shown that dopamine, administered at a dose of 2.5 -3.0 µg/kg/min, 12 to 24 hours following CM exposure, prevented nephrotoxicity from affecting individuals with mild renal dysfunction 112,113 . But results from these studies are limited because of the small number of patients and short follow-up.…”
Section: Dopaminementioning
confidence: 60%
“…This administration rate, a dose of 3-5 µg/kg/min is often called 'renal dose' or 'low-dose' dopamine and is thought to minimize the spillover stimulation of α-and β-adrenergic receptors [12]. Weisberg et al found that low dose dopamine did not prevent the contrast media induced nephropathy [26], but Hans et al proposed that dopamine treatment protected renal function from worsening by contrast media [10]. Dopamine is the endogenous precursor of norepinephrine that stimulates β 1 -receptors and dopamine receptors [4].…”
Section: Discussionmentioning
confidence: 99%